(untitled) (Praxis Educativa, 2012)
The study of teaching practices can be identified through three different approaches: the teacher that plans his/her lesson from the perspective of the didactic studies of the 50s and 60s, with emphasis on lesson planning; the study of the reflexive processes carried out by the teacher after a lesson, especially developed during the 70s and 80s; and the studies that analyze spontaneous teacherís actions during lessons, his/her intuitions and practical wisdom. This article begins with the analysis of the above mentioned approaches in order to identify teachersí ways of introducing technology in the classroom and adopting different criteria of use or re-use. A distinction is made between technological devices developed for teaching purposes and those developed to other ends. The article also distinguishes between what we call ësilent technologiesí- didactic proposals that place emphasis on the material itself and its inherent value, and ësilenced technologiesí- those cases in which the message that is transmitted is ignored and technology is used to promote thinking processes. Those situations in which pedagogical proposals are stressed or in which, on the contrary, they are trivialized due to the introduction of technological devices are also distinguished. Finally, we acknowledge that teaching practices with the aid of technology are implied in didactic proposals and so the ways in which reflection is promoted in the classroom open up a communicative channel, which allows for the contruction of knowlege, generating a space of respec and help in the dificutand complex task of teaching and learning.